The comparison of the patient satisfaction on health service quality for general and Insurance and Social Security (BPJS) patients at public health center - Ima Kristina Yulita; Florentina Kusyanti (International Journal of Health Science and Technology, 2022)
This research aims determine the comparison and relationship between the quality of health services and patient satisfaction. This type of research is quantitative with a cross sectional approach to 130 patients at the Magelang District Public Health Center. The study population was patients who were examined at the general polyclinic of the Public Health Center. Data was collected by means of a questionnaire. Data analysis was done by descriptive analysis, independent sample t test and Chi Square. The results showed that the quality of health services is good, patients are satisfied with the services provided, general patients and insurance and social security (BPJS) patients evaluated that there was no difference in the quality of health services and satisfaction, there was no relationship between the quality of health services and patient satisfaction.